Effectiveness of popular scientific books “Ethnopharmacology of the Balinese community in Barambai Kolam Kanan Village” to train students’ critical thinking skill - Ninawati Ninawati; Danang Biyatmoko; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Students need to be trained in critical thinking by developing teaching materials based on local potential, one of which is popular scientific books (PSB) that support the application of knowledge and critical thinking skills in understanding the surrounding environment. This research aims to test the effectiveness of PSB based on local potential regarding the ethnopharmacology of the Balinese community in Barambai Kolam Kanan Village in training students' critical thinking skills. This study is research into the development of formative evaluation based on the Tessmer design which focuses on students' critical thinking skills using a rubric of five indicators including interpretation, assumptions, deduction, argument evaluation, and inference. The effectiveness test subjects involved 5 students (expected effectiveness) and 20 students (actual effectiveness). The research results are based on the hope effectiveness test (small group) of the developed PSB with an average value of 64.0. Meanwhile, the actual effectiveness test (field test) obtained an average score of 73.7, increasing to 89.1. So the average N-gain value is 0.6 which is in the medium category. This illustrates that BIP based on local potential has been effectively implemented in learning to improve critical thinking skills.AbstrakBerpikir kritis mahasiswa perlu dilatih dengan mengembangkan bahar ajar berbasis potensi lokal salah satunya buku ilmiah populer yang mendukung penerapan pengetahuan serta keterampilan berpikir kritis dalam pemahaman lingkungan sekitar. Penelitian ini bertujuan menguji keefektivan BIP berbasis potensi lokal tentang Etnofarmakologi masyarakat Bali di Desa Barambai Kolam Kanan dalam melatih keterampilan berpikir kritis mahasiswa. Kajian ini adalah penelitian pengembangan evaluasi formatif berdasarkan desain Tessmer yang berfokus pada keterampilan berpikir kritis mahasiswa dengan menggunakan rubrik lima indikator meliputi interpretasi, asumsi, deduksi, evaluasi argumen, dan inferensi. Subjek uji keefektivan melibatkan 5 orang mahasiswa (keefektivan harapan) dan 20 orang mahasiswa (keefektivan aktual). Hasil penelitian berdasarkan uji keefektivan harapan (small group) terhadap BIP yang dikembangkan dengan nilai rata-rata 64,0. Sedangkan uji keefektivan aktual (field test) mendapatkan nilai rata-rata 73,7 meningkat menjadi 89,1. Maka nila rata-rata N-gain sebesar 0,6 yang berada pada kategori sedang. Hal tersebut menggambarkan BIP berbasis potensi lokal telah efektif dilaksanakan dalam pembelajaran dalam meningkatkan keterampilan berpikir kritis.